Expression of DMRT1 in Quail Embryos (Coturnix coturnix japonica) - Kusumawati, Asmarani; Istiyawati, Ninik; Aldora, Alice; Prihatno, Surya Agus; Gustari, Sri; Budiyanto, Agung (Fakultas Kedokteran Hewan Universitas Gadjah Mada, 2018)
The sex differen tiation in the quail is a complex process of fom1ation nnd involves many genes. One of lhe genes suspecred of having a major influence on gcniral fomJarion is D.MRTI. This study a1med to see Lhe level of DMRTJ gene expression in the quail embryo. The sample of rhe study was rhe gonadal tissue of quail embryos obtained from Lhe fertile quai l eggs. Eggs are inc11bated and taken dally to be isolnred from rhe gonadal genetic maleria l. Genetic material in the fonn or-DNA wns used for molecular sexing using CHDW gene. RNA was used to measure the expression of DMRTJ gene in quail embryo. Measmement of gene expression on days 1-8 was confirmed by nanodrop spectrophotomeler. The results show thar DMRTI gene expression hus differences in male and female embryos. DMRTJ gene expression in male embryos has higher intensity than females. DA1RTJ gene is also seen lo have maximum expression in male embryo's aged 3-5 days. This DMRT/ gene may have ao imponant role in the process of gemtal fonnnrion and differentiation of quail embryos, especially in males.